2013
DOI: 10.1371/journal.pone.0056200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Capsicum annuum Genetic Diversity and Population Structure Based on Parallel Polymorphism Discovery with a 30K Unigene Pepper GeneChip

Abstract: The widely cultivated pepper, Capsicum spp., important as a vegetable and spice crop world-wide, is one of the most diverse crops. To enhance breeding programs, a detailed characterization of Capsicum diversity including morphological, geographical and molecular data is required. Currently, molecular data characterizing Capsicum genetic diversity is limited. The development and application of high-throughput genome-wide markers in Capsicum will facilitate more detailed molecular characterization of germplasm c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
109
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 57 publications
13
109
0
Order By: Relevance
“…The results obtained in this study are in close agreement with those of Uddin et al (2015), who recorded highly significant variability among different chilli genotypes in Bangladesh. The current results of morphological evaluation of chilli germplasm are supported by the study of Hill et al (2013). The findings of Hornero-Méndez et al (2002), Thul et al (2009) and Ibiza et al (2012) further strengthen the current findings, who also found valuable and highly significant and positive variability among their studied genotypes.…”
Section: Individual Fruit Weightsupporting
confidence: 82%
“…The results obtained in this study are in close agreement with those of Uddin et al (2015), who recorded highly significant variability among different chilli genotypes in Bangladesh. The current results of morphological evaluation of chilli germplasm are supported by the study of Hill et al (2013). The findings of Hornero-Méndez et al (2002), Thul et al (2009) and Ibiza et al (2012) further strengthen the current findings, who also found valuable and highly significant and positive variability among their studied genotypes.…”
Section: Individual Fruit Weightsupporting
confidence: 82%
“…The genus Capsicum includes the peppers and chilies, has a great nutritional and economic value, and is widely grown in the whole world (HILL et al, 2013). Brazil is a diversity center for the genus, housing domesticated, semi-domesticated and wild species (MOSCONE et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…are cultivated worldwide and have wide applications in food and medicine industries (Hill et al 2013). The principal phytochemical compounds of peppers, namely, capsaicinoids, flavonoids, anthocyanins, vitamins C and E, phenolics, carotenoids, and dietary fibers, are active components that impart considerable health benefits (Gonzalez-Aguilar et al 2008;Park et al 2010;Zimmer et al 2012).…”
Section: Introductionmentioning
confidence: 99%